Comparing three complete mitochondrial genomes of the moss genus Orthotrichum Hedw. Issue 1 (1st January 2016) - Vigalondo, Beatriz; Liu, Yang; Draper, Isabel; Lara, Francisco; Garilleti, Ricardo; Mazimpaka, Vicente; Goffinet, Bernard
Abstract: Here, we present a comparative analysis of the mitochondrial genome of three representatives of Orthotrichum Hedw (Bryophyta): two populations of O. diaphanum and one of the related species, namely O. macrocephalum . Their mitochondrial genomes share the same gene content and gene order, and are furthermore structurally identical to those of other arthrodontous mosses. The mitogenome of the allopatric samples of O. diaphanum differ in 0.1% of their sequence, with protein coding genes holding five mutations, including two non-synonymous changes. The divergence between the mitogenomes of the two species, O. diaphanum and O. macrocephalum, is 0.4%. Within a broader sampling of the Orthotrichaceae, patterns of genome divergence are consistent with phylogenetic relationships.